2016
DOI: 10.1016/j.hfc.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biological Therapies Targeting Heart Failure

Abstract: Article synopsis Recovery of ventricular function occurs in a subset of patients with advanced heart failure treated with medical and/or mechanical therapy. Finding strategies that induce ventricular recovery through induction of repair, regeneration of ‘rejuvenation’ is a long sought goal of research programs. Cell-based strategies, use of recombinant growth and survival factors, and gene delivery are under investigation. In this brief review we highlight a few of the biological approaches in development to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Furthermore, clinical trials have demonstrated both acute and chronic improvements in cardiac function and hemodynamics following administration of recombinant human NRG to patients with HF and LVSD. Phase II clinical trials involving the EGF-domain only fragment of NRG have demonstrated increases in LVEF with decreases in end systolic volume (ESV) and end diastolic volume (EDV) among patients with HF and improvements in hemodynamics (increase in cardiac output by 30%, decrease in systemic vascular resistance by 20%, and decrease in pulmonary artery wedge pressure by 30%) in patients with stable HF (10, 11, 16). Single dose administration of GGF2 in 40 patients with HF demonstrated a dose-dependent improvement in LVEF lasting 90 days following infusion with no adverse events leading to withdrawal of the study (9).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, clinical trials have demonstrated both acute and chronic improvements in cardiac function and hemodynamics following administration of recombinant human NRG to patients with HF and LVSD. Phase II clinical trials involving the EGF-domain only fragment of NRG have demonstrated increases in LVEF with decreases in end systolic volume (ESV) and end diastolic volume (EDV) among patients with HF and improvements in hemodynamics (increase in cardiac output by 30%, decrease in systemic vascular resistance by 20%, and decrease in pulmonary artery wedge pressure by 30%) in patients with stable HF (10, 11, 16). Single dose administration of GGF2 in 40 patients with HF demonstrated a dose-dependent improvement in LVEF lasting 90 days following infusion with no adverse events leading to withdrawal of the study (9).…”
Section: Discussionmentioning
confidence: 99%
“…The provision of cell-free components, such as exosomes enriched in proteins, mRNAs, and miRNAs characteristic of parental SCs, therefore represents a potential approach for treating cardiovascular diseases [42]. Although the mechanisms by which exosomes improve cardiac function remain to be determined, these results support the concept that they constitute the main mediators of SC paracrine effects [32,43] and that a paracrine mechanism is sufficient to elicit functional recovery in cell-based therapies for post-infarctionrelated chronic heart failure [44,45].…”
Section: Mechanism(s) Of Sc-mediated Cardioreparative Effectsmentioning
confidence: 98%
“…The host of factors synthetized within SCs and released into the extracellular milieu is usually referred to as the SC secretome. To date, MSC secretome analysis has identified >200 unique proteins [31]; notably, SC secretome components are not only confined to proteins but also include mRNA and miRNAs [32].…”
Section: Mechanism(s) Of Sc-mediated Cardioreparative Effectsmentioning
confidence: 99%
“…The reviews [ 102 , 103 ] discuss research in which attempts were made at recovery of ageing myocardium through induction of cell “rejuvenation”. These reviews consider both genetic modification and effects of various viability and growth factors, such as follistatin-like 1 (FSTL1), growth-differentiation factor 11 (GDF11), and insulin-like growth factor 1 (IGF-I).…”
Section: Attempts At Experimental Cell “Rejuvenation” To Stimulatementioning
confidence: 99%